Playing While Black. (27th December 2018) - Pinckney, Harrison P.; Outley, Corliss; Brown, Aishia; Theriault, Daniel
Abstract: In the United States, black youth face unique challenges that shape "where" they recreate, "who" they participate with, and "how" they engage in recreation. Recent events around the country have highlighted the potential of racial profiling in leisure settings. As a result, black youth and parents remain aware of the potential dangers of participating in recreation activities in public spaces. As black youth and their families are forced to navigate these realities, our field is presented with opportunities to explore unanswered questions about the relationship between Race and leisure, especially in the area of youth development. Using multiple contemporary examples to demonstrate the impact of Race on the recreation of black youth, three theoretical frameworks are presented that may help advance the discussion on race, recreation, and youth development. Warning: This article includes videos that contain graphic content and may be upsetting to some.